2020
DOI: 10.1136/bmjopen-2020-042963
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the uptake and delivery of the NHS Health Check programme in England, using primary care data from 9.5 million people: a cross-sectional study

Abstract: ObjectivesTo describe the uptake and outputs of the National Health Service Health Check (NHSHC) programme in England.DesignObservational study.SettingNational primary care data extracted directly by NHS Digital from 90% of general practices (GP) in England.ParticipantsIndividuals aged 40–74 years, invited to or completing a NHSHC between 2012 and 2017, defined using primary care Read codes.InterventionThe NHSHC, a structured assessment of non-communicable disease risk factors and 10-year cardiovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 12 publications
3
63
1
Order By: Relevance
“…Although national uptake rates generally increased over this period, there was significant regional variation, with uptake rates calculated for upper-tier LA areas ranging from 25.1% to 84.7%. 8 These findings are in line with previous analyses that have identified significant variation in invitation and uptake rate for the programme, 9 and variation in Health Check delivery and follow-up, including referrals to lifestyle services. 10 11 At present, minimal national data exist to explain these differences, yet it is important to determine what does work, for whom and in what setting.…”
Section: Open Accesssupporting
confidence: 90%
See 1 more Smart Citation
“…Although national uptake rates generally increased over this period, there was significant regional variation, with uptake rates calculated for upper-tier LA areas ranging from 25.1% to 84.7%. 8 These findings are in line with previous analyses that have identified significant variation in invitation and uptake rate for the programme, 9 and variation in Health Check delivery and follow-up, including referrals to lifestyle services. 10 11 At present, minimal national data exist to explain these differences, yet it is important to determine what does work, for whom and in what setting.…”
Section: Open Accesssupporting
confidence: 90%
“…7 The largest and most recently published analysis of national data relating to the programme found that almost 10 million eligible people were offered an NHS Health Check between 2012 and 2017. 8 Of these, 52.6% (just over 5 million) took up the offer. Although national uptake rates generally increased over this period, there was significant regional variation, with uptake rates calculated for upper-tier LA areas ranging from 25.1% to 84.7%.…”
Section: Open Accessmentioning
confidence: 99%
“…27 NHS Digital data on NHS Health Checks 2012-2018, did not include new diagnoses and treatments and statin prescribing was almost twice as high as in this and previous studies, indicating major methodological differences. 28 No socioeconomic difference in attendance was reported, 28 while our study reported a small reduction by deprivation quintile Q1/2 17.9% compared to 16.0% in more deprived quintiles Q4/5. Differences may arise from different deprivation scores or population estimates.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 50%
“…Women of breast screening age in the UK are also eligible for assessment of CVD and T2D risk assessment as part of the NHS Health Check. Current coverage and outcomes for this programme are sub-optimal as it is mainly opportunistic (12). Recent Public Health England reports estimate that only 49% of adults with raised cholesterol and 57% with hypertension have been identi ed.…”
Section: Introductionmentioning
confidence: 99%